2021
DOI: 10.1177/10398562211014224
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and ECT – a Victorian perspective

Abstract: Objectives: (i) to describe the operational strategies implemented to practise electroconvulsive therapy (ECT) safely, and (ii) to explore the effect of the lockdown and operational strategies on the characteristics of patients who received ECT during the initial 6 months of the COVID-19 lockdown. Methods: At first, the operational strategies that were implemented at the Broadmeadows ECT suite were summarised. Subsequently, the characteristics of patients who received ECT in the lockdown period (16 March–16 Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…10 Another single-site study from Australia reported that an ECT team that usually included multiple psychiatrists was reduced to just the ECT director at the beginning of the pandemic. 25 Our study identified that staff safety, in relation to their infection risk, was the primary reason for intentional reductions in ECT staff numbers.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…10 Another single-site study from Australia reported that an ECT team that usually included multiple psychiatrists was reduced to just the ECT director at the beginning of the pandemic. 25 Our study identified that staff safety, in relation to their infection risk, was the primary reason for intentional reductions in ECT staff numbers.…”
Section: Discussionmentioning
confidence: 89%
“…The literature suggests that anxiety among ECT staff in relation to COVID-19 infection is common. 11,25 Effective communication between service leaders and staff may alleviate anxiety. 25 However, the nature of this communication and the extent of its impacts remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bag-mask ventilation during ECT produces aerosolization of respiratory secretions that pose a high risk of disease transmission during the outbreak of a contagious, airborne virus ( 4 ). Clinicians have attempted to overcome these issues in a number of ways; using adjusted PPE protocols, or delaying and reducing ECT treatments ( 5 , 6 ). Patients may also be considered medically unfit to receive ECT, and alternative treatments for catatonia must be delivered.…”
Section: Introductionmentioning
confidence: 99%
“…ECT treatment rooms required extra ventilation and cleaning between patients (5). ECT anesthesia aerosol-generating procedure (9), and this limited where ECT could be performed and necessitated changes in anesthetic technique (10,11). In many services, time-intensive pre-treatment COVID-19 screening was introduced (11).…”
Section: Introductionmentioning
confidence: 99%